Precise Extraction of Charge Carrier Mobility for Organic Transistors. (23rd September 2019) - Xu, Yong; Li, Yun; Li, Songlin; Balestra, Francis; Ghibaudo, Gerard; Li, Wenwu; Lin, Yen‐Fu; Sun, Huabin; Wan, Jing; Wang, Xinran; Guo, Yufeng; Shi, Yi; et al.
Abstract: Unreliable mobility values, and particularly greatly overestimated values and severely distorted temperature dependences, have recently hampered the development of the organic transistor field. Given that organic field‐effect transistors (OFETs) have been routinely used to evaluate mobility, precise parameter extraction using the electrical properties of OFETs is thus of primary importance. This review examines the origins of the various mobilities that must be determined for OFET applications, the relevant extraction methods, and the data selection limitations, which help in avoiding conceptual errors during mobility extraction. For increased precision, the review also discusses device fabrication considerations, calibration of both the specific gate‐dielectric capacitance and the threshold voltage, the contact effects, and the bias and temperature dependences, which must actually be handled with great care but have mostly been overlooked to date. This review serves as a systematic overview of the OFET mobility extraction process to ensure high precision and will also aid in improving future research. Abstract : This review focuses on mobility extraction using the organic transistor's current‐voltage characteristics. Unlike the vailable literature, this paper commences from the perspective of device physics to improve the fundamental understanding of the mobility. The physical origin, extraction methods, data selection limitations, consideration for device fabrication and parameter calibration, contact effects, and bias and temperature dependences are systematically discussed.